HIV-1 latency: From acquaintance to confidant - Chenbo Yang; Ling Tong; Jing Xue (Journal of Virus Eradication)
Antiretroviral therapy (ART) has transformed HIV from a fatal disease into manageable circumstance. However, the HIV reservoirs remain a main barrier to complete cure. This review emphasized when, where and how the latency is established, with focus on various host factors and viral proteins. We highlight the importance of Tat and Rev in facilitating the export and stability of HIV latency. We discuss how transcription factors such as NFκB, NFAT, and Sp1 regulate HIV gene expression during T cell activation, while other factors like MRTFB, BACH2, FOXO1, HMGB1, SAMHD1, APOBEC3, TRIM5, Wnt/β-catenin and LEDGF/p75 also contribute to the persistence of reservoirs. Recent studies have also identified novel restriction and immune regulatory factors such as, LAPTM5, KRT72, and CARD8, directly or indirectly influencing HIV 1 latency. The advancements in CRISPR screening technology have also identified novel host factors, such as FBXO34, FTSJ3, TMEM178A, NICN1, PEBP1, ZNF304 and ORC1, that are associated with HIV-1 latency. These findings underscore the multifaceted nature of viral latency and ongoing need for research to develop effective strategies for viral eradication.